QTL mapping for pest and disease resistance in cassava and coincidence with some introgression regions derived from M. glaziovii - Nzuki, I.; Katari, M.S.; Bredeson, J.V.; Masumba, E.; Kapinga, F.; Salum, K.; Mkamilo, G.S.; Shah, Tushaar; Lyons, J.B.; Rokhsar, D.S.; Rounsley, S.; Myburg, A.A.; et al. (Frontiers Media, 2017)
Genetic mapping of quantitative trait loci (QTL) for resistance to cassava brown streak disease (CBSD), cassava mosaic disease (CMD), and cassava green mite (CGM) was performed using an F1 cross developed between the Tanzanian landrace, Kiroba, and a breeding line, AR37-80. The population was evaluated for two consecutive years in two sites in Tanzania. A genetic linkage map was derived from 106 F1 progeny and 1,974 SNP markers and spanned 18 chromosomes covering a distance of 1,698 cM. Fifteen significant QTL were identified; two are associated with CBSD root necrosis only, and were detected on chromosomes V and XII, while seven were associated with CBSD foliar symptoms only and were detected on chromosomes IV, VI, XVII, and XVIII. QTL on chromosomes 11 and 15 were associated with both CBSD foliar and root necrosis symptoms. Two QTL were found to be associated with CMD and were detected on chromosomes XII and XIV, while two were associated with CGM and were identified on chromosomes V and X. There are large Manihot glaziovii introgression regions in Kiroba on chromosomes I, XVII, and XVIII. The introgression segments on chromosomes XVII and XVIII overlap with QTL associated with CBSD foliar symptoms. The introgression region on chromosome I is of a different haplotype to the characteristic “Amani haplotype” found in the landrace Namikonga and others, and unlike some other genotypes, Kiroba does not have a large introgression block on chromosome IV. Kiroba is closely related to a sampled Tanzanian “tree cassava.” This supports the observation that some of the QTL associated with CBSD resistance in Kiroba are different to those observed in another variety, Namikonga.